Analisis Aspek-Aspek Sosial Cerpen Liang Galang Makolang Karya Ni Putu Ayu Suaningsih - Dita Mustika Putri, Ni Made Ayu (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This study examines a short story titled Liang Galang Makolang, which appears in the short story collection Ngetélang Getih Kaang Putih, written by Ni Putu Ayu Suaningsih. The objective of this research is to describe the social aspects reflected in the short story Liang Galang Makolang. The study employs a literary sociology approach based on the theoretical framework proposed by Ratna. The research method and techniques are divided into three stages: (1) data collection utilizes the observational method supported by note-taking and translation techniques; (2) data analysis applies a qualitative method assisted by descriptive-analytical techniques; and (3) the presentation of research findings uses an informal method supported by both deductive and inductive techniques. The results of this study reveal several social aspects within the short story, including aspects of kinship, economic conditions, love and compassion, and morality.